RESTORATIVE JUSTICE IN HANDLING CRIMINAL ACTS OF NARCOTICS WITH CHILD PERFORMERS IN CONFLICT WITH THE LAW - Mugia Yarry Juanda; Zulkarnein Koto; Marsudin Nainggolan (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
Narcotics crimes are not only committed by adults but also children. For cases of criminal acts committed by children, the restorative justice system at least aims to repair/recover criminal acts committed by children with actions that are beneficial to children. This research is included in normative juridical research. The data used is secondary data. Meanwhile, the collection of legal materials is carried out by reviewing and collecting library materials and the analysis method is carried out using a qualitative descriptive method. From the results of the study, it can be concluded that based on the three decisions that the researchers reviewed, namely Decision Number 28/Pid.Sus-Anak/2020/PN Mre with the Defendant Andesta Bin Rusimin, Decision No.02/Pid.Sus-Anak/2015/PN- SAB with the Defendant Fajri Bin Nurdin and Decision Number 06/Pid.Sus.anak/2017/PN-Bir with the Defendant Child, it can be seen that the concept of restorative justice in handling cases of children as perpetrators of narcotics crimes by the panel of judges was not implemented. This can be seen in his injunction; the Panel of Judges actually sentenced the Defendant to years in prison. Whereas the concept adopted by restorative justice is a concept that prioritizes recovery, not retaliation. The ideal concept of restorative justice in handling cases of children as perpetrators of narcotics crimes is a concept that provides a value of justice for both perpetrators and victims, for this reason it is necessary to reform Law Number 35 of 2009 regarding sanctions for child perpetrators of narcotics crimes by eliminating criminal sanctions. imprisonment is half of the adult sentence. It is necessary to build rehabilitation places that specifically deal with children who are perpetrators of narcotics crimes.